2014
DOI: 10.1159/000360991
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus in Oropharyngeal Cancer: A Multicenter Study in Japan

Abstract: Background: The incidence rates of oropharyngeal squamous cell carcinoma (OPSCC) have risen steadily in the USA and in northern Europe. These increases are thought to be a consequence of persistent infection with high-risk human papillomavirus (HPV) in OPSCC patients. HPV is an emerging etiologic factor in OPSCC. In Japan, the incidence of OPSCC has significantly increased over the last three decades. However, the population of HPV-positive OPSCC patients is currently unknown. We examined the nationwide trends… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 19 publications
3
49
2
Order By: Relevance
“…Thus, in this study, experienced pathologists in our hospital defined patients with the immune-positive cell ratio of 25% or more in tumor cells as having p16 positivity, according to previous report (15). In this study, the p16-positive rate was 43.75%, which is in line with previous data (9,20,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 86%
“…Thus, in this study, experienced pathologists in our hospital defined patients with the immune-positive cell ratio of 25% or more in tumor cells as having p16 positivity, according to previous report (15). In this study, the p16-positive rate was 43.75%, which is in line with previous data (9,20,(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 86%
“…For example, almost all cases of HPV-positive HNC (1) are found to originate in the oropharynx, particularly in the palatine and lingual tonsils, (2) are not associated with smoking or drinking, and (3) are more common in comparatively young age groups [3][4][5][6] . Additionally, the primary tumour is discovered comparatively early or while it is still small, although in many cases it has already progressed to cervical LN metastasis, and these LN lesions frequently cause cystic changes [19] .…”
Section: Discussionmentioning
confidence: 99%
“…Using PCR-based methods, Mineta et al showed that 23 % of all HNSCC showed HPV positivity and OPSCC was the most common (54 %) site [39]. The incidence of HPV-related OPSCC has been increasing year by year, from 30 % to 54 % [16,[40][41][42]. The Osaka University reported the trend of HPV infection incidence in tonsillar and base of tongue carcinomas.…”
Section: Prevalence Of Hpv In Hnsccmentioning
confidence: 99%
“…HPV 16 is associated with the majority of OPSCCs in the United States, Europe, and Japan [6,7,11,15,16]. Indeed, a good amount of evidence has been accumulated suggesting that HPV-related OPSCC has special characteristics distinct from OPSCC not related to HPV.…”
Section: Introductionmentioning
confidence: 99%